Microbiota characterization of the green mussel Perna viridis at the tissue scale and its relationship with the environment - Chen, Liying; Li, Dai; Shen, Yawei; Li, Zhuo; Hao, Huanhuan; Ke, Caihuan; Meng, Zhang; Feng, Danqing (Frontiers in Microbiology, 2024)
Research on the microbiota associated with marine invertebrates is important for understanding host physiology and the relationship between the host and the environment. In this study, the microbiota of the green mussel Perna viridis was characterized at the tissue scale using 16S rRNA gene high-throughput sequencing and compared with the microbiota of the surrounding environment. Different mussel tissues were sampled, along with two environmental samples (the mussel's attachment substratum and seawater). The results showed that the phyla Proteobacteria, Bacteroidetes, and Spirochaetae were dominant in mussel tissues.The bacterial community composition at the family level varied among the tissues of P. viridis. Although the microbiota of P. viridis clearly differed from that of the surrounding seawater, the composition and diversity of the microbial community of the foot and outer shell surface were similar to those of the substratum, indicating their close relationship with the substratum. KEGG prediction analysis indicated that the bacteria harbored by P. viridis were enriched in the degradation of aromatic compounds, osmoregulation, and carbohydrate oxidation and fermentation, processes that may be important in P. viridis physiology. Our study provides new insights into the tissue-scale characteristics of mussel microbiomes and the intricate connection between mussels and their environment.